Elementary Teacher Candidates' Views of Children's Literature on Climate Change - Catherine Lammert (MDPI AG, 2024)
In today's elementary classrooms, students face an uncertain future, standing to inherit a world characterized by environmental unsustainability. Therefore, elementary teachers must educate their students on anthropogenic climate change to increase the likelihood that future generations will mitigate its risks. This article documents the perspectives on children's literature depicting climate change held by 27 Teacher Candidates in a conservative, oil-producing region of a U.S. state. The results show a low likelihood of participants self-censoring the topic of climate change compared with other frequently censored topics (i.e., gender, sexuality, and race). However, they report accepting others' views on climate change even when those views contradict settled climate science. This implies a need for more directed preparation for elementary teachers to actively negotiate with their students to ensure they develop research-aligned perspectives on climate change.